MELK Inhibition Effectively Suppresses Growth of Glioblastoma and Cancer Stem-Like Cells by Blocking AKT and FOXM1 Pathways - Zhang, Xu; Wang, Jie; Wang, Yifeng; Liu, Guanzheng; Li, Huan; Yu, Jiefeng; Wu, Runqiu; Liang, Jun; Yu, Rutong; Liu, Xuejiao (Frontiers in Oncology, 2021)
Glioblastoma multiforme (GBM) is a devastating disease yet no effective drug treatment has been established to date. Glioblastoma stem-like cells (GSCs) are insensitive to treatment and may be one of the reasons for the relapse of GBM. Maternal embryonic leucine zipper kinase gene (MELK) plays an important role in the malignant proliferation and the maintenance of GSC stemness properties of GBM. However, the therapeutic effect of targeted inhibition of MELK on GBM remains unclear. This study analyzed the effect of a MELK oral inhibitor, OTSSP167, on GBM proliferation and the maintenance of GSC stemness. OTSSP167 significantly inhibited cell proliferation, colony formation, invasion, and migration of GBM. OTSSP167 treatment reduced the expression of cell cycle G2/M phase-related proteins, Cyclin B1 and Cdc2, while up-regulation the expression of p21 and subsequently induced cell cycle arrest at the G2/M phase. OTSSP167 effectively prolonged the survival of tumor-bearing mice and inhibited tumor cell growth in in vivo mouse models. It also reduced protein kinase B (AKT) phosphorylation levels by OTSSP167 treatment, thereby disrupting the proliferation and invasion of GBM cells. Furthermore, OTSSP167 inhibited the proliferation, neurosphere formation and self-renewal capacity of GSCs by reducing forkhead box M1 (FOXM1) phosphorylation and transcriptional activity. Interestingly, the inhibitory effect of OTSSP167 on the proliferation of GSCs was 4-fold more effective than GBM cells. In conclusion, MELK inhibition suppresses the growth of GBM and GSCs by double-blocking AKT and FOXM1 signals. Targeted inhibition of MELK may thus be potentially used as a novel treatment for GBM.